Viral Infection in Adults with Severe Acute Respiratory Infection in Colombia - Remolina, Yuly Andrea; Ulloa, María Mercedes; Vargas, Hernán; Díaz, Liliana; Gómez, Sandra Liliana; Saavedra, Alfredo; Sánchez, Edgar; Cortés, Jorge Alberto (PLOS ONE, 2015)
Objectives To identify the viral aetiology in adult patients with severe acute respiratory infection (SARI) admitted to sentinel surveillance institutions in Bogotá in 2012. Design A cross-sectional study was conducted in which microarray molecular techniques for viral identification were used on nasopharyngeal samples of adult patients submitted to the surveillance system, and further descriptions of clinical features and relevant clinical outcomes, such as mortality, need for critical care, use of mechanical ventilation and hospital stay, were obtained. Setting Respiratory infections requiring hospital admission in surveillance centres in Bogotá, Colombia. Participants Ninety-one adult patients with acute respiratory infection (55% were female). Measurements Viral identification, intensive care unit admission, hospital stay, and mortality. Results Viral identification was achieved for 63 patients (69.2%). Comorbidity was frequently identified and mainly involved chronic pulmonary disease or pregnancy. Influenza, Bocavirus and Adenovirus were identified in 30.8%, 28.6% and 18.7% of the cases, respectively. Admission to the intensive care unit occurred in 42.9% of the cases, while mechanical ventilation was required for 36.3%. The average hospital stay was 9.9 days, and mortality was 15.4%. Antibiotics were empirically used in 90.1% of patients. Conclusions The prevalence of viral aetiology of SARI in this study was high, with adverse clinical outcomes, intensive care requirements and high mortality.